Ethnomedicinal plants used to cure jaundice in Kammam District of Andhra Pradesh, India - T.V.V. Seetharami Reddi, Ratna Manjula, R., J. Koteswara Rao* and (Journal of Phytology, 2011)
Twenty eight species included in 27 genera and 20 families are used to cure jaundice by the tribals of Khammam district, Andhra Pradesh. Half of the plants are herbs and one fourth trees. Euphorbiaceae and Cucurbitaceae are the dominant families. The ethnomedicinal practices involved plants ranging from one to five.